VALUE CHAIN OF ENERGY: A CONCEPTUAL PICTURE - FERRAGI, Eder Moreno; SHIBUYA, Marcelo (Revista Brasileira de Engenharia de Biossistemas, 2011)
This paper discusses subject of high importance like the utilization of natural resources in development activities of high added value, especially for countries latecomers in the global development process. Raises some questions such as: The concept of governance of global value chain can help in the right appropriation of the natural resource values that are the basis for many other value chains? What tools should use, and what position should assume the agents who want to hold the governance through ownership of the considered key assets for several other value chains - resource-driven governance? What should be the role of the State related to the "resource nationalism" in order to catch-up with other economies? To provide a conceptual basis for which such issues can be more specific and profound discussed, the aim is to provide a conceptual generic framework through the value chain of an essential resource for all other value chains – the energy